On rough deferred statistical convergence for sequences in neutrosophic normed space - Mursaleen, M.; Kişi, Ömer; Gurdal, Mehmet; Kişi, Ömer (Univ Nis, Fac Sci Math, 2024)
In this study, we provide the notion of rough deferred statistical convergence for sequences within the framework of the neutrosophic normed space (NNS). We also study the notion of rough deferred statistical cluster points for sequences in NNS and discuss how this cluster points set and the set of rough deferred statistical limit points related to the aforesaid convergence relate to each other.
Keywords: Neutrosophic Normed Space; Rough Convergence; Deferred Statistical Convergence